Navigating the Atlantic: Brazil’s defense engagements with Africa in the South Atlantic - Leal Ribeiro De Albuquerque, Felipe (2016)
Brazil’s recent inroads towards Africa reflect one façade of the country’s greater aspirations. Ranging from technical cooperation projects and a push for dynamic commercial relations to the promotion of inter-regional dialogues, Brazil’s presence in Africa also comprises initiatives in the security realm. Not receiving matching attention, endeavors in the security domain reveal Brazil’s aspiration of building the South Atlantic as a region in which South America and Africa can foster common ground, preclude extra-regional powers, secure maritime resources and develop naval defense industry. Amidst this background, I argue Brazil engaged in securitization practices in order to promote shared understandings and cooperation in both sides of the South Atlantic. In this work, I confront bilateral cooperation projects with African partners with the recent multilateral revitalization of the Zone of Peace and Cooperation of the South Atlantic (ZOPACAS) in order to attest to which extent Brazil was able to succeed in region-building practices and could conform a coherent grand strategy. The conclusion confirms the existence of a disconnection between the bilateral and multilateral dimensions of Brazil’s engagements, which undermines the region-building process and minimizes the ability of this country to act in the South Atlantic.